Regional Regulation of the Mayor of Kendari Number 16 of 2014 concerning Smokefree Areas: A VRIO Analysis Approach - Elfirah; Rini; Aswanty; Wiwied Tri Dayanti (Journal of Law, Social Science and Management, 2025)
Background: Smoking has long been entrenched in Indonesian society, making cessation efforts particularly challenging. This behavior not only poses significant health risks to active smokers but also endangers non-smokers through secondhand smoke exposure. The incidence of non-communicable diseases (NCDs), both globally and nationally, continues to rise. According to the 2023 Indonesian Health Survey, in Southeast Sulawesi Province, 2.0% of individuals aged ≥10 years reported smoking daily, 1.2% smoked occasionally, 0.2% were former smokers, and 96.6% had never smoked. To protect the public from tobacco smoke, Kendari City enacted Regional Regulation No. 16 of 2014 on Smokefree Areas. Objective: This study aims to analyze the implementation of Kendari City Regional Regulation No. 16/2014 using the VRIO framework (Value, Rarity, Imitability, Organization) to assess policy effectiveness and formulate recommendations. Methods: A descriptive qualitative approach was applied, utilizing literature review as the primary method. Data were sourced from the official regulation document and relevant supporting literature. The VRIO analysis was used to examine internal and external factors influencing policy implementation. Results: The regulation holds strategic value in promoting public health and environmental quality. While similar regulations exist elsewhere in Indonesia, this policy offers a broader and more integrated scope. Its conceptual clarity and structured organizational support enhance replicability in other regions. Conclusion: Regulation Number 16/2014 serves as a vital instrument for tobacco control in Kendari City. Its successful implementation depends on sustained collaboration among government institutions, civil society, and community stakeholders.  Keywords: Smoking, Public Policy, Tobacco Control, VRIO Analysis